Influência das rotas de síntese nas propriedades estruturais, morfológicas e termoluminescentes de LaAlO3 puro e dopado com íons terras-raras - Silveira, Iury Santos (2020)
This work presents a comparative study on production routes of pure and doped lanthanum aluminate (LaAlO3) with rare earth ions that was synthesized by different routes of synthesis. Pechini and combustion synthesis were the routes used as a reference, as they are already well known; in addition to these, variations in synthesis via sol-gel were used. For the synthesis via sol-gel, three different complexing agents of natural origin were used: coconut oil, copaiba oil and coconut water. LaAlO3 has perovskite structure, that is broadly studied due to the possibility of crystal lattice defects that improve its luminescence properties, besides serving as a good host to dopants elements. Pure LaAlO3 samples in single crystalline phase were obtained from 600 ºC using coconut water, in the samples obtained via Pechini this phase occurred from 700 ºC, and 800 ºC for the other synthesis routes, all calcined for 4 hours. The doping of LaAlO3 was made by replacing the lanthanum ions (La3+) with cerium ions (Ce3+) and dysprosium (Dy3+) at concentrations of 5% and 1%, respectively. In the doped samples, the single crystalline phase was obtained from 1000 ºC for 4 hours. The structural characterization was carried out by X-ray diffraction technique (XRD), aided by the crystallographic refinement with the Rietveld method; FTIR and Raman spectroscopy techniques also aided in this characterization. Morphological characterization was performed with scanning electron microscopy (SEM) and elemental characterization by means of energy dispersive X ray spectroscopy (EDX). For optical characterization, optical absorption techniques were used in the ultraviolet and visible region (Uv-Vis) and photoluminescence spectroscopy (PL). Finally, the thermoluminescent response (TL) was analyzed after irradiations with X-ray beams, gamma radiation of 137Cs and different wavelengths of ultraviolet radiation. The results on PL showed that there was contamination of samples with europium (Eu3+), and TL results show that pure so-called samples presented more intense TL signal than samples doped with Ce and Dy. Despite contamination, it was possible to understand on the TL signal behavior for different types of radiation and evaluate for which radiation beam the samples exhibit the most intense TL response.